KINEMATICAL FEATURES OF FORMATION OF A FLANGE WITH MINIMUM TENSION OF A TRANSIENT TOROIDAL SURFACE - M. I. Sidorenko (Литьë и металлургия)
The technology of plastic forming of wide flanges in tube billets with the predicted length of the transitional toroidal section between the outer plane of the flange and the internal cavity of the pipe is proposed. The procedure for calculating the length of this section is given. In order to eliminate the toroidal portion in the flange formed during the flanging of the pipe, it is proposed to perform its plastic shaping by depositing the cylindrical part of the workpiece. Equations for calculating the extent of the free surface on the toroidal part of the workpiece when it is shaped, depending on the coefficient of contact friction and the presence of a radial support of the flange are obtained. The variant of forming in the flange the toroidal section in the stamp with the compensation cavity is proposed. Equations for calculating the deformation force and the extent of the free surface are given.